Keyboarding for computer success - Jerry W. Robinson (South-Western Education Pub., 1999)
Digitacion para el dominio de la computadora is perfect for Spanish-speaking users who want to master the English keyboard. This 30-lesson book teaches the keys and provides practice with review lessons, skill checks, and assessment exercises. The directions throughout the text are in Spanish, while the actual activities being keyed are still in English